Enhancement of electrical properties of vanadyl phthalocyanine derivative by PCBM. Issue 3 (5th May 2015) - Aziz, F.; Sulaiman, K.; Al-Rawi, Wissam Khayer; Ahmad, Z.; Sayyad, M.H.; Karimov, Kh. S.; Wei, L.L.; Tahir, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effect of [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) on improvement of physical and electrical properties of vanadyl phthalocyanine derivative. The correlation between the physical characteristics of the active layers, comprising vanadyl 2, 9, 16, 23-tetraphenoxy-29H, 31H-phthalocyanine (VOPcPhO) and PCBM, and the electrical properties of metal/organic/metal devices have been studied. The use of soluble vanadyl phthalocyanine derivative makes it very attractive for a variety of applications due to its tunable properties and high solubility. Design/methodology/approach – The sandwich type structures Al/VOPcPhO/Al and Al/VOPcPhO:PCBM/Al were fabricated by spin casting the active organic layers between the top and bottom (aluminum) electrodes. The stand-alone (VOPcPhO) and composite (VOPcPhO:PCBM) thin films were characterized by X-ray diffraction, atomic force microscopy, UV/Vis and Raman spectroscopy. The electronic properties of the metal/organic/metal devices were studied using current-voltage (I-V) characteristics in dark at room temperature. Findings – The values of barrier height for Al/VOPcPhO/Al and Al/VOPcPhO:PCBM/Al devices were obtained from the forward bias I-V curves and were found to be 0.7 eV and 0.62 eV, respectively. The present study indicates that the device employing VOPcPhO:PCBM composite film as the active layer, with better structural and morphological characteristics, results in reduced barrier height at the metal-organic film interface as compared to the one fabricated with the stand-alone film. Research limitations/implications – It is shown that doping VOPcPhO with PCBM improves the crystallinity, morphology and junction properties. Practical implications – The spin coating technique provides a simple, less expensive and effective approach for preparing thin films. The soluble VOPcPhO is conveniently dissolved in a number of organic solvents. Originality/value – The physical properties of the VOPcPhO:PCBM composite thin film and the electrical properties of the composite thin-film-based metal/organic/metal devices have not been reported in the literature, as far as our knowledge is concerned.